Identifikasi Komoditi Unggulan Tembakau Dalam Meningkatkan ‎Profit Perekonomian Masyarakat Desa Wateswinangun Kecamatan ‎Sambeng - Widodo, Arif; Sa’adah, Eva Zahrotus; Al-Irsyad, Ahmad Assyayud; Sugiantoro, Ahmad Bagus (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2022)
The purpose of writing this paper is to describe the superior commodity of tobacco in increasing the community’s economic profit. The period for carrying out this activity lasts for two months, from August 2022 – September 2022. The author uses the PAR (Participation Action Research) method. The results obtained are that the tobacco products produced by Wateswinangun Village have super quality as a superior commodity.